Pollination of a slippery lady slipper orchid in south-west China: Cypripedium guttatum (Orchidaceae) - Hans Bänziger (2018)
Cypripedium guttatum was studied in north-west Yunnan at 3490 m a.s.l. The flowers are rewardless 'kettle traps'. The structure of the lip, where pollinators are temporarily kept prisoner, and the method of their capture, are unusual in being Paphiopedilum- rather than Cypripedium-like. The deceptive orchid does not mimic any of the diverse flowers concurrently blooming in the habitat, all being visited by the polylectic pollinators of C. guttatum, viz. Lasioglossum virideglaucum, L. clypeinitens and L. sauterum, besides two additional probable pollinators and four non-pollinating visitors (all Halictidae; three new species). The bees got caught when they tried to climb onto the staminode and their forelegs slid down its slippery downward ridges, causing them to tumble to the pouch bottom. To leave, they had to climb a tunnel leading past the stigma to the anthers where a pollen smear was acquired while extruding themselves from the narrow exit. The similarities with myiophylous Paphiopedilum are discussed in view of the possibility that they may foreshadow evolutionary transitions between melittophily and myiophily found in slipper orchids. © 2005 The Linnean Society of London.